Struktur Tegakan dan Sebaran Jenis Terentang (Campnosperma auriculata) dan Mendarahan (Knema laurina) di Hutan Rawa Gambut - Istomo Istomo; Abdul Aziz (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Peat swamp forests in Indonesia have an important role as a water provider, water storage, carbon storage, and as a place to live for flora and fauna. Terentang (Campnosperma auriculata) and mendarahan (Knema laurina) are some of the main trees in peat swamp ecosystem. This research aims to determaine stand structure and distribution of terentang and mendarahan species in peat swamp forests. The research was conducted at Sebangau National Park and Sungai Bram Itam Peatland Protected Forest using the vegetation analysis method with a plot size of 100 m x 100 m, divided into sub-plots size 20 m x 20 m, and used for data collection for trees with size ≥ 10 cm. The results in Sebangau National Park was 115 individuals of terentang, 10 individuals of mendarahan and total of all species was 1043 individuals. while in the Sungai Bram Itam Peatland Protected Forest was 5 individuals of terentang, 21 individuals of mendarahan and total of all species was 543 individuals. The stand structure at both locations classified as normal. The spreading pattern of Terentang and mendarahan trees is a uniform distribution pattern. Keywords: Campnosperma auriculata, Knema laurina, Peat swamp, Species distribution, Stand structure